1996
DOI: 10.1097/00005392-199602000-00003
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Diet on Urinary Stone Disease

Abstract: Appropriate dietary manipulation may be beneficial in the prevention of recurrent urolithiasis in only a select group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 86 publications
3
31
1
Order By: Relevance
“…Fellström et al [23] found higher alcohol consumption in 20 stone patients compared to controls, but this observation was not confirmed by others [24]. Parivar et al [25] suggested that alcohol consumption in moderation is not a significant risk factor for urolithiasis. Nevertheless, based on our results, we suggest that restriction of alcohol drinking may be beneficial for the prevention of upper urinary calculi; this is especially important for those who had a positive family history of stone.…”
Section: Discussionmentioning
confidence: 92%
“…Fellström et al [23] found higher alcohol consumption in 20 stone patients compared to controls, but this observation was not confirmed by others [24]. Parivar et al [25] suggested that alcohol consumption in moderation is not a significant risk factor for urolithiasis. Nevertheless, based on our results, we suggest that restriction of alcohol drinking may be beneficial for the prevention of upper urinary calculi; this is especially important for those who had a positive family history of stone.…”
Section: Discussionmentioning
confidence: 92%
“…A lower daily water intake would decrease the urine output, resulting in increased urine saturation and promoting crystalline precipitation and UC development. In contrast, a large intake of water could increase the urine output and reduce the concentrations of calcium, oxalate, and urate (Parivar et al, 1996). Meanwhile, a higher amount of water could also prevent the polymerization of urinary mucin, thereby reducing the likelihood of kidney stone formation (Borghi et al, 1999).…”
Section: Analysis Of Relevant Factors In 115 Cases Of <7-year-old Uygmentioning
confidence: 99%
“…Increased dietary sodium intake, and hence urinary sodium excretion, promotes calciuria both via renal mechanisms and increased calcium mobilization from bone [ 66 ] . Higher urinary sodium excretion also correlates with increased uric acid excretion and decreased citrate excretion, both of which promote crystallization.…”
Section: Dietary Factorsmentioning
confidence: 99%